CORRELATION OF SANITATION HOUSE CONDITIONS, DRINKING WATER ACCESS, AND HEALTHY CLEAN BEHAVIOUR WITH DIARRHOEA - Dewi Lusyana Sari (Jurnal Berkala Epidemiologi, 2019)
Background: The incidence of diarrhoea is still a public health problem in various districts or cities in East Java Province. The prevalence of diarrhoea in Probolinggo Regency in 2017 was 2.43%. Purpose: This study aims to determine the strong relationship between conditions of home sanitation, drinking water access, and clean and healthy living behaviour with the incidence of diarrhoea in Probolinggo District. Methods: This is an observational analytic study with a correlation study design. The population used was all diarrhoea patients treated by health workers from all health centres in each subdistrict in Probolinggo in 2017. The variables studied included the percentage of home sanitation conditions, drinking water access, clean and healthy living behaviour, and prevalence of diarrhoea from all puskesmas (government health clinics) in the district of Probolinggo. The data analysis technique used was Pearson correlation. Results: The prevalence of diarrhoea in Probolinggo Regency decreased in the three years 2015 to 2017, with Bago Health Centre contributing the highest number of cases. This study shows a very weak correlation between the conditions of home sanitation (0.07), drinking water access (0.02), and clean and healthy living behaviour (0.03) and the incidence of diarrhoea. Conclusion: In 2017 there was a very weak correlation between the conditions of home sanitation, drinking water access, and clean and healthy living behaviour with the incidence of diarrhoea in Probolinggo District. The Probolinggo District Health Office and related sectors should pay attention to the dominant factors that have a positive linear correlation direction in order to prevent the incidence of diarrhoea